1987
DOI: 10.1055/s-2007-1020248
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Efficacy of Transsternal Thymectomy in Myasthenia Gravis

Abstract: Between January 1977 and September 1985, 75 patients in our department underwent elective surgery for myasthenia gravis through a median sternotomy. The main prerequisite was optimal stabilization by medical treatment with the best possible vital capacity. The Osseman types were as follows: type I (22), type IIa (19), type IIb (26), type III (7), and type IV (1). All patients, except for 3 who were mechanically ventilated for a few hours after surgery, were immediately extubated at the end of the operation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
7
1
1
Order By: Relevance
“…2). In contrast to our experience and that of others [5, 9, 14, 15, 16, 17], several authors found a significant trend towards a greater remission rate in patients with a shorter duration of symptoms and/or an early age at the time of surgery [6, 11, 12, 18, 19, 20]. The majority of these series contained few or no patients with thymoma [6, 12, 18, 19].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…2). In contrast to our experience and that of others [5, 9, 14, 15, 16, 17], several authors found a significant trend towards a greater remission rate in patients with a shorter duration of symptoms and/or an early age at the time of surgery [6, 11, 12, 18, 19, 20]. The majority of these series contained few or no patients with thymoma [6, 12, 18, 19].…”
Section: Discussioncontrasting
confidence: 51%
“…Although some authors found better results in young [6, 12, 22, 23]and/or female [9, 23]patients, the majority found no influence of these two factors [5, 7, 8, 9, 10, 11, 14, 15, 16, 17, 18, 19]. Therefore, sex, age and other factors such as the presence of acetylcholine receptor antibody [22]or the presence of other autoimmune disorders [23]are less likely to influence the rate of improvement after thymectomy and should not intervene with the decision to perform thymectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only infrequentl y has minor morbidity been deta iled (15)(16)(17), In recent studies, no mortality was encounte red. irrespect ive of surgical app roach (6 -17).…”
Section: Mortality and Morbidityin Transcervical And Thoracoscopic Thmentioning
confidence: 98%
“…Há relatos dessa complicação nas cirurgias transcervicais (32) e por esternotomia. (33) Bulkley et al, (20) realizando timectomia "máxima" por cervicoesternotomia, relataram três pacientes com disfonia persistente e um com transitória. O controle clínico fácil observado em 90,4% dos casos, após média de 39,2 meses de acompanhamento, demonstra resultados animadores do método.…”
Section: Discussionunclassified